Commodities of care : the business of HIV testing in China - Fan, Elsa L. (University of Minnesota Press, 2021)
"How global health practices can end up reorganizing practices of care for the people and communities they seek to serve"-- Provided by publisher.
Keywords: HIV infections -- Prevention -- Economic aspects -- China.; AIDS (Disease) -- Prevention -- Economic aspects -- China.; Gay men -- Health and hygiene -- China.; Gay men -- China -- Social conditions.; HIV infections -- Diagnosis -- China.; AIDS (Disease) -- Diagnosis -- China.; Medical economics -- China.; Public health -- China.; Infections à VIH -- Prévention -- Aspect économique -- Chine.; Sida -- Prévention -- Aspect économique -- Chine.; Homosexuels masculins -- Santé et hygiène -- Chine.; Homosexuels masculins -- Chine -- Conditions sociales.; Économie de la santé -- Chine.; Santé publique -- Chine.; SOCIAL SCIENCE / Gay Studies; AIDS (Disease) -- Diagnosis; Gay men -- Health and hygiene; Gay men -- Social conditions; HIV infections -- Diagnosis; Medical economics; Public health; China